Surfce Functionalized via AdLAMA3 Multilayer Coating for Re-epithelization Around Titanium Implants - Zhang, Jing; Li, Yongzheng; Li, Jialu; Shi, Yuan; Hu, Jinxing; Yang, Guoli (Frontiers in Bioengineering and Biotechnology, 2020)
The peri-implant epithelium (PIE) forms a crucial seal between the oral environment and the implant surface. Compared with the junctional epithelium (JE), the biological sealing of PIE is fragile, which lacks hemidesmosomes (HDs) and internal basal lamina (extracellular matrix containing laminin332, IBL) on the upper part of the interface. In the study, we aim to prepare a coating with good biocompatibility and ability to immobilize the recombinant adenovirus vector of LAMA3 (AdLAMA3) for promoting the re-epithelization of PIE. The titanium surface functionalized with AdLAMA3 was established via layer-by-layer assembly technique and antibody-antigen specific binding. The biological evaluations including cell adhesion and the re-epithelization of PIE were investigated. The results in vitro demonstrated that the AdLAMA3 coating could improve epithelial cell attachment and cell spreading in the early stage. In vivo experiments indicated that the AdLAMA3 coating on the implant surface has the potential to accelerate the healing of the PIE, and could promote the expression of laminin α3 and the formation of hemidesmosomes. This study might provide a novel approach and experimental evidence for the precise attachment of LAMA3 to titanium surfaces. The process could improve the re-epithelization of PIE.